Current status of HTLV-1 carrier in Japanese pregnant women. (February 2014) - Suzuki, Shunji; Tanaka, Masanobu; Matsuda, Hideo; Tsukahara, Yuki; Kuribayashi, Yasushi; Gomibuchi, Hideto; Miyazaki, Ryoichiro; Kamiya, Naoki; Nakai, Akihito; Kinoshita, Katsuyuki
Abstract We examined the current status of human T-cell leukemia virus type 1 (HTLV-1) carrier in Japanese pregnant women, according to the results of HTLV-1 screening and confirmation tests of women who gave birth in Japan in 2011. We requested 2642 obstetrical facilities to provide information of HTLV-1 tests and 71.3% of them responded. Considering the response rate and the rate of implementation of confirmation tests, the number of HTLV-1 carrier in Japanese pregnant women was estimated to be 1620 (0.16%) per year.